Zebrafish studies identify serotonin receptors mediating antiepileptic activity in Dravet syndrome. Issue 1 (1st August 2019) - Griffin, Aliesha L; Jaishankar, Priyadarshini; Grandjean, Jean-Marc; Olson, Steven H; Renslo, Adam R; Baraban, Scott C
Abstract : Serotonin drugs, including clemizole, have recently emerged as potential treatment options for Dravet syndrome. We synthesized a library of clemizole analogues and screened for anti-seizure activity using the zebrafish Dravet syndrome model. Coupled with in vitro binding, we identified 5-HT2B receptors as a mediator in the mechanism of seizure suppression. Abstract: Dravet syndrome is a life-threatening early-onset epilepsy not well controlled by antiepileptic drugs. Drugs that modulate serotonin (5-HT) signalling, including clemizole, locaserin, trazodone and fenfluramine, have recently emerged as potential treatment options for Dravet syndrome. To investigate the serotonin receptors that could moderate this antiepileptic activity, we designed and synthesized 28 novel analogues of clemizole, obtained receptor binding affinity profiles, and performed in vivo screening in a scn1lab mutant zebrafish ( Danio rerio ) model which recapitulates critical clinical features of Dravet syndrome. We discovered three clemizole analogues with 5-HT receptor binding that exert powerful antiepileptic activity. Based on structure–activity relationships and medicinal chemistry-based analysis, we then screened an additional set of known 5-HT receptor specific drug candidates. Integrating our in vitro and in vivo data implicates 5-HT2B receptors as a critical mediator in the mechanism of seizure suppression observed in Dravet syndrome patients treated with 5-HT modulating drugs. Graphical Abstract: